The Effect of Rare Earth Elements Holmium, Gadolinium and Zinc on Microstructure of Aluminium LM30 Alloy - Alinan, Ali Luqman; Ahmad, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study explores the practical applications of aluminum alloys in various manufacturing sectors, focusing specifically on the advantages of incorporating rare earth elements to enhance corrosion resistance and improve the microstructure of these alloys. It begins with an introductory section that highlights the study's relevance within the broader industrial context. The study also includes a comprehensive literature review, examining both the historical and contemporary uses of aluminum alloys and the impact of rare earth elements on their microstructure and corrosion resistance.